Determining the utility of standard hospital microbiology testing: Comparing standard microbiology cultures with DNA sequence analysis in patients with chronic sinusitis. Issue 2 (1st June 2019) - Rapoport, Sarah K.; Smith, Alyssa J.; Bergman, Maxwell; Scriven, Kelly A.; Brook, Itzhak; Mikula, Suzette K.
Abstract : Objective: To demonstrate DNA sequencing analysis (DNAsa) of sinus cultures in patients with CRS is a reliable method of detecting pathogens in polymicrobial CRS infections. Methods: After obtaining Institutional Review Board approval for this prospective cohort study, we selected a random sample of 50 patients with CRS at Medstar Georgetown University Hospital between September 2016 and March 2017. We defined CRS as a history of rhinosinusitis refractory to maximal medical therapy and prior endoscopic sinus surgery. Patients demonstrating active purulence in a sinus cavity were prospectively selected to undergo standard hospital cultures (SHC) and DNAsa cultures. Organisms identified in both methods were compared for each patient. Results: Specimens were obtained from 29 female and 16 male patients with a mean age of 50 years. A total of 45 cultures were included in our final analysis; five cultures were excluded after inappropriate laboratory processing. Results from these patients were compared and analyzed. Cohen's weighted kappa analysis showed agreement between the two testing methods in identifying predominant microorganisms. DNAsa detected 31.9% more microorganisms compared to SHC ( P  < 0.05). When multiple microorganisms were detected, DNAsa yielded more positive results compared to SHC ( P  < 0.05). Conclusions: DNAsa detects all microorganisms identified by SHC as well as predominant microorganisms not detected by SHC. Thus molecular pathogen identification may be more reliable for identifying multiple microorganisms as compared to standard culture techniques that identify only one or two microorganisms. In recalcitrant cases of CRS, DNAsa may provide better guidance in selection of appropriate antimicrobial treatment.